225k views
5 votes
What is the value of the expression

-X^2 - 4x - 6 when
X = -2?

2

18

-18

-2

1 Answer

2 votes

Answer:


\boxed{\sf -2}

Step-by-step explanation:


\sf Evaluate \: - {x}^(2) - 4x - 6 \: where \: x = - 2: \\ \sf \implies - {x}^(2) - 4x - 6 = - {( - 2)}^(2) - 4( - 2) - 6 \\ \\ \sf {( - 2)}^(2) = 4 : \\ \sf \implies - \boxed{ \sf 4} - 4( - 2) - 6 \\ \\ \sf - 4( - 2) = 8 : \\ \sf \implies - 4 + \boxed{ \sf 8} - 6 \\ \\ \sf - 4 + 8 - 6 = 8 - (4 + 6) : \\ \sf \implies 8 - (4 + 6) \\ \\ \sf 4 + 6 = 10 : \\ \sf \implies 8 - \boxed{ \sf 10} \\ \\ \sf \implies - 2

User Breno Prata
by
6.2k points